Osiem i pół Zbigniewa Osińskiego - Marek Hendrykowski, Marek Hendrykowski (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
A close reading analysis of a brilliant paper devoted to Federico Fellini’s Otto e mezzo written in 1965 by the famous Polish theatrologist, Zbigniew Osiński (1939-2017).